Home Health Care after Skilled Nursing Facility Discharge Following Heart Failure Hospitalization - Weerahandi, Himali (J Am Geriatr Soc, 2019)
BACKGROUND/OBJECTIVE: Heart failure (HF) readmission rates have plateaued despite scrutiny of hospital discharge practices. Many HF patients are discharged to skilled nursing facility (SNF) after hospitalization before returning home. Home health care (HHC) services received during the additional transition from SNF to home may affect readmission risk. Here, we examined whether receipt of HHC affects readmission risk during the transition from SNF to home following HF hospitalization. DESIGN: Retrospective cohort study. SETTING: Fee-for-service Medicare data, 2012–2015. PARTICIPANTS: Beneficiaries 65 and older hospitalized with HF who were subsequently discharged to SNF then discharged home. MEASUREMENTS: The primary outcome was unplanned readmission within 30 days of discharge to home from SNF. We compared time to readmission between those with and without HHC services using a Cox model. RESULTS: Of 67,585 HF hospitalizations discharged to SNF and subsequently discharged home; 13,257 (19.6%) were discharged with HHC, 54,328 (80.4%) without. Patients discharged home from SNF with HHC had lower 30-day readmission rates than patients discharged without HHC (22.8% vs 24.5%, p<0.0001) and a longer time to readmission. In adjusted model, hazard for readmission was 0.91 (0.86 – 0.95) with receipt of HHC. CONCLUSIONS: Recipients of HHC were less likely to be readmitted within 30 days versus those discharged home without HHC. This is unexpected, as patients discharged with HHC likely have more functional impairments. Since patients requiring a SNF stay after hospital discharge may have additional needs, they may particularly benefit from restorative therapy through HHC; however only about 20% received such services.